Optimal design of gas injection development method for enhanced recovery in terrestrial shale oil reservoir - Cui, Xiaoyu; Chen, Zhewei; Wang, Rui; Han, Yi; He, Xujiao; Lei, Zhengdong (Frontiers in Energy Research, 2024)
This study investigates the shale oil drainage characteristics from the Gulong Sag, The objective is to clarify the development method for effective recovery enhancement of terrestrial shale oil. The investigation employs elastic depletion, CO2 displacement, and CO2 huff and puff coupled with nuclear magnetic resonance (NMR) measurements and numerical simulation methods. The study found that the elastic depletion, CO2 displacement, and CO2 huff and puff utilization efficiencies were 17.4%, 18.87%, and 21%, respectively. The study evaluated the oil drainage efficiency of different pore sizes in elastic depletion and CO2 huff and puff modes. The results demonstrated a clear trend in the order of micropore, mesoporous and macropore, with micropores exhibiting the highest oil drainage efficiency due to gas channeling during CO2 displacement. The use of CO2 huff and puff has been shown to improve oil drainage efficiency by 6.02%∼9.2% for different pore sizes. The numerical simulation optimization results suggest an injection volume of 3,000 t per round per well, an injection rate of 100 t/d, and a soaking time of 20 d for optimal CO2 huff and puff injection. This will increase oil production by 65,000 m³, resulting in an overall improvement of 24%. The study results provide a strong theoretical foundation for improving the recovery rates of terrestrial shale oil and gas through injection.